Le accuse del sinedrio a Gesù - Jossa, Giorgio 1938- (2024)
Giorgio Jossa writes this article based on his belief that the statement in Mark’s Gospel about the existence of two Sanhedrin meetings on the night before Jesus’ crucifixion is truly historical. According to Jossa, Mark is convinced that Jesus’ answer to Caiaphas’ question about his Messianic claim was considered blasphemous by the high priest. However, Jesus was not condemned to death by the Sanhedrin (in the supposed night meeting). The Sanhedrin allegedly decided to turn Jesus over to Pilate on the charge of making himself king, and on that charge Pilate sentenced him to death.
Keywords: Sanhedrin - Caiaphas - Jesus’; s Gospel; s process - Gospel of Mark - Historical Value of Mark’